What derives female labor force participation in Muslim countries? A generalized method of moments inference - Bilal Mehmood; Sama Ahmad; Muhammad Imran (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Globalization and its social consequences have engendered newer trends that include increasing preferences of women to become economically active. Economic role of women has become a widely discussed topic in recent times in Muslim world. There are different perspectives and norms that determine their decision to become economically active i.e. to join the labor force. Hardly any study addresses this question with reference to Muslim world. Considering the emergence and rise of female employment in Muslim world, this paper formulates an empirical framework for the factors that affect female labor force participation (FLFP). Data is extracted from international databases World Development Indicators (WDI). For 41 Muslim countries the data was available for the time span of 2003-2013. To conduct rigorous statistical analysis of the relevant variables; we use a widely accepted robust estimation technique, known as Generalized Method of Moments (GMM). Findings of this study provide specific recommendations that are helpful in managing the emerging trends of women employment in Muslim world.
Keywords: 330; female labor force participation; female employment; Muslim world